2019
DOI: 10.3389/fimmu.2019.01990
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Safety and Efficacy of Rituximab in Treating Immune-Mediated Disorders

Abstract: Background: During the past years biologic agents (also termed biologicals or biologics) have become a crucial treatment option in immunological diseases. Numerous articles have been published on biologicals, which complicates the decision making process on the use of the most appropriate biologic for a given immune-mediated disease. This systematic review is the first of a series of articles assessing the safety and efficacy of B cell-targeting biologics for the treatment of immune-mediated diseases.Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
106
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(122 citation statements)
references
References 109 publications
(167 reference statements)
2
106
0
2
Order By: Relevance
“…Possibly exposed was defined as a contact with a confirmed COVID-19 patient for more than 15 minutes, at less than 2 meters, and without adequate safety measures. Because of pre-existing comorbidities, seven patients were under immunosuppressive treatments, which comprised corticosteroids at stable doses, whereas patients taking B cell-depleting agents, such as rituximab, 22 were excluded. For longitudinal analyses of serum and mucosal SARS-CoV-2-specific antibody responses two subjects with mild COVID-19…”
Section: Human Subjects and Patient Characteristicsmentioning
confidence: 99%
“…Possibly exposed was defined as a contact with a confirmed COVID-19 patient for more than 15 minutes, at less than 2 meters, and without adequate safety measures. Because of pre-existing comorbidities, seven patients were under immunosuppressive treatments, which comprised corticosteroids at stable doses, whereas patients taking B cell-depleting agents, such as rituximab, 22 were excluded. For longitudinal analyses of serum and mucosal SARS-CoV-2-specific antibody responses two subjects with mild COVID-19…”
Section: Human Subjects and Patient Characteristicsmentioning
confidence: 99%
“…Syeda et al, similarly, found the same treatment combination (rituximab, steroids, plasma exchange) effective in a single case [20]. Kaegi et al analyzed the safety and efficacy of rituximab in multiple immune-mediated disorders [21]. The study included three patients with anti-GBM disease [21].…”
Section: Anti-gbm Diseasementioning
confidence: 99%
“…Kaegi et al analyzed the safety and efficacy of rituximab in multiple immune-mediated disorders [21]. The study included three patients with anti-GBM disease [21]. After a follow-up of 33-49 months, anti-GBM antibodies became undetectable in all three patients, and only one of the patients remained dialysisdependent [21].…”
Section: Anti-gbm Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…It has been used as a therapeutic biologic agent in B cell lymphoma and leukemia [12]. A systematic review has discussed about safety and efficacy of RTX in immune-mediated disorders [13]. A meta-analysis has shown high short-term benefit/risk ratio of RTX in AIHA [14].…”
Section: Introductionmentioning
confidence: 99%